Effects of operation schemes on hydrodynamics and thermal structure in a deep dimictic reservoir - Jia Wang; Lunyu Wu; Yuanjian Wang; Yujun Yi (Engineering Applications of Computational Fluid Mechanics, 2025)
The operation scheme significantly influences the hydrodynamic characteristics and thermal structure of reservoirs by altering regulation cycles and water level conditions, which are crucial for shaping the ecological environment. This study combines a three-dimensional numerical thermo-hydrodynamic model with the Ω-vortex identification method to investigate the evolution patterns of hydrodynamics and thermal structures in the Liujiaxia Reservoir (a deep dimictic reservoir in the upper reaches of the Yellow River), under two actual and two projected operation schemes. The results reveal that the phase relationship between water level and velocity exhibits a rope-like temporal variation, controlled by the operation scheme and influenced by upstream inflows. Different schemes impact surface heat accumulation and thermal stratification, where optimised schemes can alleviate stratification intensity. Large-scale vortices influence the distribution of water temperature by elevating the surface water temperature in their central regions during summer and lowering it during winter, while also enhancing the temperature gradient within the thermocline in the vortex-affected areas. Furthermore, the spatiotemporal distribution of vortices is influenced by the operation scheme through its alteration of the backwater effect on the downstream water level. This study elucidates the coupling mechanisms of hydrodynamics and thermal structures under varying schemes, providing insights into optimising reservoir regulation and ecological management strategies.